Organization spiritual support, burnout, and well-being in child welfare settings - Wilke, Nicole Gilbertson (Journal of management, spirituality & religion, 2025)
This study examined how organizations' faith identity, perceived organizational support for spiritual practices, and perceived ability to implement those practices predict wellbeing and professional quality of life among child welfare professionals. A total of 262 professionals working with vulnerable children and families completed standardized measures. Results indicated that branding as a faith-based organization alone did not predict well-being outcomes. However, perceived support for spiritual practices was associated with higher life satisfaction and lower burnout, and perceived ability to engage in spiritual practices predicted greater resilience and compassion satisfaction. Results also indicate that both religious commitment and perceived personal capacity to enact spiritual practices were associated with higher life satisfaction, resilience, compassion satisfaction and lower burnout. Findings highlight the importance of tangible, accessible spiritual support over formal organizational identity alone. They also suggest that the capacity to enact spiritual practices is essential to receiving their benefits.